2011
DOI: 10.33549/physiolres.931903
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Receptors – From Molecular Biology to Clinical Applications

Abstract: Serotonin (5-hydroxytryptamine) is an ubiquitary monoamine acting as one of the neurotransmitters at synapses of nerve cells. Serotonin acts through several receptor types and subtypes. The profusion of 5-HT receptors should eventually allow a better understanding of the different and complex processes in which serotonin is involved. Its role is expected in the etiology of several diseases, including depression, schizophrenia, anxiety and panic disorders, migraine, hypertension, pulmonary hypertension, eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
141
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(165 citation statements)
references
References 67 publications
2
141
0
11
Order By: Relevance
“…It has been reported that 5-HT 1B receptor subtypes are Gi/o protein-coupled, and are negatively coupled adenylyl cyclase (AC) pathway, reducing cAMP (Bouhelal et al, 1988;Pytliak et al, 2011). Actually, 5-HT 1B receptor-mediated long-term depression has been reported to be dependent on AC pathway (Mathur et al, 2011).…”
Section: K + Channel Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 5-HT 1B receptor subtypes are Gi/o protein-coupled, and are negatively coupled adenylyl cyclase (AC) pathway, reducing cAMP (Bouhelal et al, 1988;Pytliak et al, 2011). Actually, 5-HT 1B receptor-mediated long-term depression has been reported to be dependent on AC pathway (Mathur et al, 2011).…”
Section: K + Channel Modulationmentioning
confidence: 99%
“…Actually 5-HT-related drugs, especially selective serotonin uptake inhibitors (SSRIs), are clinically used for ameliorating the symptoms in such disorders (Bandelow et al, 2008). However, the mechanisms underlying the overall roles of central 5-HT systems as well as the action of medications for the treatment of anxiety disorders are still ambiguous, probably due to the diversity of central 5-HT receptors (Pytliak et al, 2011). Therefore, analyses in the levels of cellular neurophysiology regarding the roles of 5-HT receptor subtypes are essential for the better understandings of central 5-HT systems in the control of mood or anxiety behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…65 The 5-HT1B/1D receptors by which triptans are believed to exert their benefits in the treatment of migraine are G-protein-coupled receptors. 66 Schurks et al 67 determined whether a common polymorphism in the gene for the G-protein b3 subunit (GNB3) C825T modulated responder rates to triptans among a cohort of 231 unrelated patients with cluster headaches. Results suggested that the effectiveness of triptans was associated with heterozygous carriers of the GNB3 825T allele.…”
Section: Therapeutic Biomarkersmentioning
confidence: 99%
“…Common psychiatric comorbidity among migraine sufferers has also been reported (Breslau and Davis, 1993;Merikangas and Stevens, 1997;Ortiz et al, 2010). Imbalance in serotonin (5-HT) neurotransmission is one of the possible factors linking pathophysiology of migraine (Hamel, 2007) with other disorders such as depression, anxiety, epilepsy and schizophrenia (Hedlund, 2009;Pytliak et al, 2011). Sumatriptan, a 5-HT1 receptor agonist, traditionally used in migraine, modulates increased levels of brain serotonin that occurs during migraine attacks (Sakai et al, 2008).…”
Section: Introductionmentioning
confidence: 99%